INOVASI PROGRAM DESA SIAP DAN LANCIP (LAYANAN CEPAT, EMPATIK, DAN PRO AKTIF) DI DESA LOWAYU KECAMATAN DUKUN KABUPATEN GRESIK - Dandi Syifa Al Karimi; Meirinawati Meirinawati (Universitas Negeri Surabaya, 2022)
The development of technology has made government officials begin to develop public services, one ofwhich is in Lowayu village, Dukun sub-district, Gresik Regency through the Ready and Taper VillageProgram. This program offers a number of services related to population administration that can becompleted at the village level, so that people do not need to come directly to the Dispendukcapil Officein Gresik Regency. The purpose of this study is to describe the Ready and Taper Village ProgramInnovations in Lowayu village. The focus of this research uses the theory by Bugge et al (2018). Datacollection techniques using interview techniques, documentation, and observation. The research focusanalysis refers to the success factors of an innovation in the public sector consisting of 6 (six) indicatorsincluding governance and innovation; source of ideas for innovation; innovation culture; capabilitiesand tools; goals, outcomes, drivers, barriers; and collect single information data. The results of the studyshow, from the governance and innovation indicators that the regulatory system or policy used is inaccordance with the predetermined rules. Sources of innovation ideas are obtained from internalorganizations and external organizations. The culture of innovation provides convenience to thecommunity in managing population administration which can be completed at the village level.Innovation capabilities and tools have good performance and functionality, supported by competentresources and complete facilities. Indicators of goals and outcomes are shortening the distance ofpopulation administration services from the apparatus to the community, the obstacle experienced isthat there are still many people who do not know the requirements proposed in the process of populationadministration services in the Ready and Taper Village program. Meanwhile, collecting singleinformation data is carried out through socialization to the community. Keywords: Public Service, Program Innovation, Population Administration, Ready and Taper Village.